Indian Subjects : Hemispheric Perspectives on the History of Indigenous Education - Child, Brenda J., 1959- (Book collections on Project MUSE., 2014)
Indian Subjects brings together an outstanding group of scholars from the fields of anthropology, history, law, education, literature, and Native studies to address indigenous education throughout different regions and eras. While histories of the devastating impact of boarding schools - and Native responses to those schools - have dominated academic and community views of indigenous educational history (and some appear in this volume, as well), the valuable lessons from these boarding school histories in the United States and Canada nonetheless provide a fairly narrow view of indigenous educational experiences. Indian Subjects pushes beyond that history toward hemispheric and even global conversations, fostering a critically neglected scholarly dialogue that has too often been limited by regional and national boundaries. Many of the contributors to Indian Subjects tackle educational experiences of their own communities, and all of them provide insightful analysis of events and structures that need to be incorporated more fully into the history of indigenous peoples and education. -- from back cover.